People with special needs in Ancient societies: a comparative study between few early philosophers and Islam - Islam, Md Sirajul; Samsudin, Sofiah (International Journal of Scientific and Research Publications, 2020)
This article focuses on people with special needs in ancient societies. The main aim of this article is to examine people with special needs in ancient societies as a comparative study between few early philosophers and Islam in order to find out the real circumstance and situation of this group of people. It focuses on three different ancient societies Europe, Arab, and India. This systematic investigation meets with ruthless and brutal decision of few philosophers, invalid notion of people; inhuman customs and picture of harassment towards disabled people in abovementioned societies. It attains only in the Holy Qur’ān and Prophetic traditions moral approaches in caring and empowering persons with special needs in early Islamic society in 7th century.